Ragam Pendekatan Dan Aliran Pemikiran Dalam Kajian Ekonomi Islam - Fikri, Muhammad; Arif, Muhammad (Journal of Student Development Informatics Management (JoSDIM), 2024)
Economic activities cannot be separated from people's lives. However, in meeting the needs mof the community, it is not permissible to do something that can harm others. This paper aims to examine Muhammad Nejatullah Siddiqi's thoughts on Islamic economics. The approach used in this paper is qualitative. Data were collected from library data, both from primary and secondary sources. Furthermore, the data were analyzed and examined from general data, then specific conclusions were drawn using inductive, deductive, and descriptive data analysis techniques. The results of the study show that Siddiqi as an economist with a mainstream school of the thought expressed his view that fulfilling the needs of Muslims must be guided by Islamic law. One's success is closely related to moral values that are implemented using the paradigm of the Qur'an.